Lessons From COVID-19: Physical Exercise Can Improve and Optimize Health Status - Cerasola, Dario; Argano, Christiano; Corrao, Salvatore (Frontiers in Medicine, 2022)
The outbreak of Coronavirus Disease 2019 [COVID-19] has caused increasing challenges for healthcare systems globally. The disease has rapidly spread from Wuhan all over the world involving more than four hundred million individuals and including more than five million deaths. In dealing with the pandemic, China and other countries, took protective measures such as promoting social distancing, cancelling public gathering, closing schools, quarantine and lockdowns. All these measures lead to physical inactivity. Being physically inactive has significant repercussions on human wellbeing and mental status and it is associated with anxiety, stress, increased chronic disease risk and worsening of chronic conditions. In this sense, the relevance of maintaining a healthy lifestyle through a physical exercise has been outlined by World Health Organization (WHO). The aim of this brief review is to discuss the importance of physical activity in the context of COVID-19 pandemic highlighting the benefits of physical activity and exercise that could be potential effective treatment strategies for comorbid chronic conditions, long covid syndrome [LCS] and symptoms such as depression and anxiety.